Taxation Aspects of Corporate Taxpayers - Ambarita, Dinar; Kusuma, Eka; Kwartani, Yunita (Pelopor Publikasi Akademika, 2024)
This research delves into the intricate taxation aspects surrounding corporate taxpayers. It examines the various dimensions of corporate taxation, including the principles governing corporate tax liabilities, tax planning strategies, and compliance obligations. The study navigates through the complexities of corporate tax regimes, analyzing the implications of tax laws, regulations, and reforms on businesses. Furthermore, it explores the evolving landscape of international taxation and its impact on multinational corporations. The paper also discusses contemporary issues such as tax avoidance, transfer pricing, and tax incentives, shedding light on their implications for corporate taxpayers and tax authorities. Through a comprehensive review of literature and case studies, this research provides valuable insights into the challenges and opportunities associated with corporate taxation, offering recommendations for policymakers, tax practitioners, and corporate entities to navigate the ever-changing tax environment effectively.